Survey of Foetal Wastages: A Case Study of Makurdi Abattoir in Benue State from 1997 to 2002 - Abdulkadir, U.; Jiya, E.Z.; Kosu, S.A. (Pakistan Journal of Nutrition, 2008)
This study was conducted to evaluate the causes and effects of foetal wastage in the Nigeria livestock industry, following indiscriminate slaughter of pregnant cows in Makurdi Abattoir, Benue State. A total of 45, 742 were slaughtered in the abattoir, with a total of 1,508 (3.9%) fetuses recovered from 1997 to 2002. There was no significant difference (P>0.05) between fetuses and years.